Analisis Faktor-Faktor yang Mempengaruhi Keterlambatan Audit (Audit Delay) - Susi Astuti (Jurnal Akuntansi dan Pajak, 2024)
The purpose of this research is to determine the factors that influence audits (audit delay). The subjects in this research are property sector companies listed on the Indonesia Stock Exchange in 208-2021. This research sample used purposive sampling. The research results show that profitability has an effect on audit delay. Meanwhile, company size, company age and audit changes have no effect on audit delay. KAP size is not able to moderate company size, company size, profitability, audit turnover and audit.